The Peace Discourse in Europe, 1900-1945 - Castelli, Alberto, author.
1 online resource (250 pages)
Keywords: This book charts ideas European intellectuals (mostly from Great Britain, France, Germany and Italy) put forward to solve the problem of war during the first half of the twentieth century: a period that began with the Anglo-Boer war and that ended with the explosion of the atomic bombs on Hiroshima and Nagasaki. Such ideas do not belong to a homogeneous tradition of thought, but can be understood as a unique discourse that takes different characteristics according to the point of view of each author and of the specific historical situation.